ANALYZING THE DETERMINANTS OF BOND MARKET DEVELOPMENT IN NIGERIA - Ajibu Jonas; Asia Khamis Nyange; Ashura Rajabu Yusuph (MESP–FEB UNS, 2024)
This study examines the key factors influencing the development of Nigeria’s bond market using time series data from 1981 to 2022. While employing quantitative methods, the study identifies a strong long-term relationship between key economic variables and bond market development. Major findings highlight the critical roles of inflation, fiscal deficit, foreign direct investment, and per capita income in shaping market growth. The study provides practical policy recommendations, including measures to boost market liquidity, improve transparency, and promote public-private partnerships for sustainable bond market development. These findings contribute significantly to understanding the dynamics of emerging bond markets and their potential for economic development in Nigeria.